A practical model for identification of children at risk of excess energy intake in the developing world. Issue 11 (8th March 2019) - Gaskin, Pamela S; Chami, Peter; Ward, Justin; Solari, Ofelia Gabriela Bernales; Sing, Bernd; Jackson, Maria D; Broome, Hedy
Abstract: Objective: We describe diet quality by demographic factors and weight status among Barbadian children and examine associations with excess energy intake (EI). A screening tool for the identification of children at risk of excess EI was developed. Design: In a cross-sectional survey, the Diet Quality Index–International (DQI-I) was used to assess dietary intakes from repeat 24h recalls among 362 children aged 9–10 years. Participants were selected by probability proportional to size. A model to identify excess energy intake from easily measured components of the DQI-I was developed. Setting: Barbados. Participants: Primary-school children in Barbados. Results: Over one-third of children were overweight/obese, and mean EI for boys (8644 (se 174·5) kJ/d (2066 (se 41·7) kcal/d)) and girls (8912 (se 169·9) kJ/d (2130 (se 40·6) kcal/d)) exceeded the RDA. Children consuming a variety of food groups, more vegetables and fruits, and lower percentage energy contribution from empty-calorie foods showed reduced likelihood of excess EI. Intake of more than 2400 mg Na/d and higher macronutrient and fatty acid ratios were positively related to the consumption of excess energy. A model using five DQI-I components (overall food group variety, variety for protein source, vegetables, fruits and empty calorie intake) had high sensitivity for identification of children at risk of excess EI. Conclusions: Children's diet quality, despite low intakes of fruit and vegetables, was within acceptable ranges as assessed by the DQI-I and RDA; however, portion size was large and EI high. A practical model for identification of children at risk of excess EI has been developed.